Study of Assistance Development of Thematic Learning Material by Integrating New Literacy and Disaster Literacy on Science Teachers - Asrizal Asrizal (Fakultas MIPA Universitas Negeri Padang, 2020)
The 4.0 industrial revolution requires humans to possess 21st century skills. Education should be able to prepare students to have 21st century skills to be successful in their life. In addition, the geographical condition of Indonesia is a disaster-prone region. For this reason, teaching should be able to develop student literacy to face the challenges of the industrial revolution 4.0 and the geographical condition of the Indonesian region. The thematic science teaching is relevant to 21st century skills, essential principles of 21st century learning, and the geographical condition of Indonesia. But the real conditions show that the integration of literacy in science teaching is still lacking and limited. A solution to solve this problem is the assistance program the development of thematic learning material by integrating new literacy and disaster literacy for science teachers in junior high school. The objective of the research is to investigate the results of the assistance program the development of thematic learning material. Participants of program assistance were 30 science teachers who were members of the Science MGMP in East Agam district. The instrument for collecting data consisted of pretest and posttest and questionnaire sheet. The data were analyzed by descriptive statistics analysis and wilcoxon signed rank test. Based on the results of data analysis can be stated that: 1). in the assistance program activities for the development of thematic science teaching material can be produced 26 teaching materials in the form of student worksheet by integrating new literacy and disaster literacy, 2). the average value of the practicality of using thematic science worksheet according to students in two junior high schools is 86.41 so that this average value can be classified into very good category, 3). the average value of participant responses to the implementation of the assistance program is 85.65 and this average value can be entered into very good category, and 4). the assistance program for developing learning material by integrating new literacy and disaster literacy is effective to improve knowledge of science teachers about data literacy, technological literacy, human literacy, and disaster literacy.